TUNJUK AJAR MELAYU; Warisan Nilai Pada Bait-Bait Syair Gurindam Dua Belas Raja Ali Haji - Mulyadi H (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Mystical literature is not only a part of the long tradition in Malay literature in archipelagos but also it is directly a integral part of policical, cultural and social practice that was conditioned, and if conditioned the discursive formation in society of Malay particularly in Pengengat Island-Kepulauan Riau province, and widely in South East Asia area. Gurindam Dua Belas Raja Ali Haji is the Islamic literary work that is characterized typically by Sufism, writing by Raja Ali Haji, an intellectual, cultural observer, Moeslem leader in 19th centuries in Pengengat Island. This Gurindam Dua Belas Raja Ali Haji is included al-irsyadi’s literary work containing the didactic-educational message for ethical and moral reconstruction of life.